PENGARUH MOTIVASI, SELF EFFICACY, DAN PEMAHAMAN PADA PERATURAN MENTERI KEUANGAN NO. 111/PMK.03/2014 TERHADAP MINAT BERKARIR MAHASISWA AKUNTANSI SEBAGAI KONSULTAN PAJAK - Via Sesaria Adyagarini; Afifudin Afifudin; Hariri Hariri (e_Jurnal Ilmiah Riset Akuntansi, 2020)
ABSTRACTThis study aims to determine the effect of motivation, self efficacy, and Understanding of Minister of Finance Regulation No. 111 / PMK.03 / 2014 on the career interests of accounting students as Tax Consultants at State and Private Universities. This type of research is an empirical study using primary data. The population of this study are undergraduate accounting students, Malang State University and Malang Islamic University. Determination of the sample using the Slovin formula with 95 respondents. Data analysis techniques were performed using multiple linear regression analysis with the help of SPSS 20.Based on the results of testing that has been done shows that simultaneous motivation, self efficacy and PMK Understanding Number 111 / PMK.03 / 2014 have a positive effect together on the career interests of accounting students as tax consultants.  Partial testing shows that only motivation and self-efficacy affect the career interests of accounting students as tax consultants whereas, Understanding of PMK Number 111/PMK.03/2014 does not affect the career interests of accounting students.Keywords: Motivation, self efficacy, Understanding of PMK Number 111 / PMK.03 / 2014 and career interests of accounting students.